Prenatal And Postnatal Risk Factors Associated with Stunting in Children Aged 0-24 Months Banyumas Regency Indonesia - Erna Kusuma Wati; Setiyowati Rahardjo; Dian Anandari (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Stunting remains a serious public health challenge in Indonesia. The prevalence of stunting in Banyumas Regency reached 20.9% in 2023. Determinants of stunting are related to many factors, both prenatal and postnatal. The purpose of this study was to analyze the risk factors for stunting in children aged 0-24 months during the prenatal and postnatal periods in Banyumas Regency in 2024. This is an observational cross-sectional study that included 100 children aged 0–24 months selected through cluster random sampling. Data analysis included univariate, bivariate with chi-square, and multivariate with multiple logistic regression. The results showed that prenatal factors associated with stunting were maternal MUAC (p=0.029), gestational weight gain (p=0.031), and postnatal factors were maternal nutritional knowledge (p=0.03), parental diet (p=0.042), and child factors were gender (p=0.034), birth weight (p=0.001), and protein adequacy (p=0.04). Multivariate analysis revealed that factors influencing stunting included maternal MUAC, gestational weight gain, parental diet, and birth weight. The most influential factor was birth weight (p=0.00; OR=12.5, meaning that babies with low birth weight are 12.5 times more likely to be stunted. The results of this study emphasize and then develop appropriate interventions during the prenatal and postnatal periods to reduce stunting.